Nuclear power in the twenty-first century - An assessment (Part 1) - Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Nuclear power was one of the most important discoveries of the twentieth century, and it continues to play an important role in twenty-first century discussions about the future energy mix, climate change, innovation, proliferation, geopolitics, and many other crucial policy topics. This paper addresses some key issues around the emergence of nuclear power in the twentieth century and perspectives going forward in the twenty-first, including questions of economics and competitiveness, the strategic choices of the nuclear superpowers and countries that plan to either phase out or start using nuclear power, to the diffusion of nuclear technologies and the emergence of regional nuclear conflicts in the "second nuclear age". The starting point for our hypothesis is the observation that nuclear power was originally developed for military purposes as the "daughter of science and warfare" (Lévêque 2014, 212), whereas civilian uses such as medical applications and electricity generation emerged later as by-products. Based upon this observation, we interpret the nuclear industry in terms of "economies of scope", where strategies, costs, and benefits must be assessed in the multiproduct context of military and civilian uses of nuclear power. We propose a classification of different economic perspectives on nuclear electricity generation, and confirm the consensus of the literature that on its own, nuclear power has never been an economic method of producing electricity: not a single reactor in existence today was constructed by a private investor in a competitive, market economic framework. The economics-of-scope perspective is a useful heuristic to interpret countries' strategic choices regarding the use of nuclear power. The paper provides a survey of strategies used by the nuclear superpowers (United States, Russia, China), by countries phasing out nuclear power because they cannot benefit from economies of scope (e.g., Italy, Spain, Germany, Sweden, Switzerland), and by potential newcomers who may expect synergies between military and civilian uses (e.g., Iran, the United Arab Emirates, Egypt, perhaps one day also Japan). We conclude that the future of nuclear power in the twenty-first century must be assessed in terms of economies of scope, and that a purely "economic" analysis of nuclear electricity is insufficient to grasp the complexity of the issue; this also raises conceptual challenges for energy modelers. The paper leaves out some important questions to be addressed in a future Part II of the assessment, such as economic and technical issues of plant decommissioning, long-term storage of waste, and the potential role of nuclear energy in climate policies.
Keywords: L52; L95; N7; Q48; Q54; 330; nuclear power; technology; competitiveness; economies of scope; geopolitics